Wellbeing as Capability: Findings in Hearing-Impaired Adolescents and Young Adults With a Hearing Aid or Cochlear Implant - Rijke, Wouter J.; Vermeulen, Anneke M.; Willeboer, Christina; Knoors, Harry E. T.; Langereis, Margreet C.; van der Wilt, Gert Jan (Frontiers in Psychology, 2022)
In the Western world, for deaf and hard-of-hearing children, hearing aids or cochlear implants are available to provide access to sound, with the overall goal of increasing their well-being. If and how this goal is achieved becomes increasingly multifarious when these children reach adolescence and young adulthood, and start to participate in society in other ways. An approach to well-being that includes personal differences and the relative advantages and disadvantages that people have, is the capability approach, as developed by Nobel Prize laureate Amartya Sen. Capability is the set of real opportunities people have to do and be things they have reason to value. We interviewed 59 young people, aged 13 through 25, with cochlear implants (37) or hearing aids (22) to capture their capability. We found that their hearing devices enabled them to actively participate in a predominantly hearing society, with few differences between cochlear implant and hearing aid recipients. They did, however, report challenges associated with prejudices and expectations, and with feeling poorly understood, all of which appeared to impact their capability. Through the lens of capability, alleged differences between hearing aid and cochlear implant recipients began to fade. We discuss the implications for initiatives focused on the long term support young recipients of hearing devices to meet their specific requirements over time.